2018
DOI: 10.32964/tj17.09.519
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and sustainability initiatives lead to improved polyaminopolyamide epichlorohydrin (PAE) wet-strength resins and paper products

Abstract: Polyaminopolyamide-epichlorohydrin (PAE) resins are the predominant commercial products used to manufacture wet-strengthened paper products for grades requiring wet-strength permanence. Since their development in the late 1950s, the first generation (G1) resins have proven to be one of the most cost-effective technologies available to provide wet strength to paper. Throughout the past three decades, regulatory directives and sustainability initiatives from various organizations have driven the development of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Examples of paper grades that benefited from the early application of PAAE are tissue and towel products, followed by liquid packaging board, tea bag and currency. Today, although PAAE is used mainly in paper products and molded pulp products, studies have shown that it can be used to protect antibody bioactivity on paperbased bio diagnostics (Huang et al 2017;Crisp and Riehle 2018;Valencia et al 2020;Qin et al 2022;Astute Analytica 2023).…”
Section: Generations Inventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of paper grades that benefited from the early application of PAAE are tissue and towel products, followed by liquid packaging board, tea bag and currency. Today, although PAAE is used mainly in paper products and molded pulp products, studies have shown that it can be used to protect antibody bioactivity on paperbased bio diagnostics (Huang et al 2017;Crisp and Riehle 2018;Valencia et al 2020;Qin et al 2022;Astute Analytica 2023).…”
Section: Generations Inventionmentioning
confidence: 99%
“…Next, the poly(aminoamide) reacts with epichlorohydrin between 20 to 40 °C to form a tertiary aminochlorohydrin. Lastly, the temperature is raised between 60 to 80 C to promote the cyclization of the aminochlorohydrin functionality to the azetidinium functionality (3-hydroxyazetidinium group), and the resulting product is further partially crosslinked to produce PAAE resin; sulfuric acid is generally used to quench the reaction (Espy 1990;Andreasson and Wågberg 2009;Crisp and Riehle 2018;Francolini et al 2023).…”
Section: Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). [27] Von ähnlichen Ergebnissen wurde im bundesweiten Monitoring 2022 sowie im Überwachungsplan 2020 berichtet. [34,35] Von besonderem Interesse ist die Feststellung, dass insbesondere beschichtete Materialien hohe Überschreitungen im KWE aufweisen können.…”
Section: Probenübersicht Und Bewertungunclassified